2019
DOI: 10.31219/osf.io/hnpsq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Growth characteristics, economics and hair mineral status of camel calves reared in different system of management

Abstract: Management systems were compared by conducting 2 trials with different feeding practices. Trials 1 and 2 were conducted by feeding guar phalgati and moth chara as manger feeding, respectively, for 165 days each to 5 camel calves each under intensive system of management (ISM) and semi-intensive system of management (SIM). Total gain in body weight was higher in SIM than ISM group in both the trials. Mean body weight and average growth rate significantly increased in SIM as compared to ISM group at the end of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 2 publications
0
6
6
Order By: Relevance
“…While in present study, lower daily weight gain was observed in IMS due to the limited supply of concentrate. Present findings are not in line with the findings of Bhakat et al (2009) who reported that the average daily gain (g/d) differed significantly among two systems, being higher in SIMS as (325 and 476 g/d) than IMS as (278 and 331 g/d) with guar phalgati (Cyamopsis tetragonoloba) and moth chara (Phaseolus aconitifolius) feeding, respectively. Bakheit et al (2012) reported significant differences in the mean daily weight gain (grams) under semi-intensive (535+9.83) and traditional management systems (TMS) (317+5.46), respectively.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…While in present study, lower daily weight gain was observed in IMS due to the limited supply of concentrate. Present findings are not in line with the findings of Bhakat et al (2009) who reported that the average daily gain (g/d) differed significantly among two systems, being higher in SIMS as (325 and 476 g/d) than IMS as (278 and 331 g/d) with guar phalgati (Cyamopsis tetragonoloba) and moth chara (Phaseolus aconitifolius) feeding, respectively. Bakheit et al (2012) reported significant differences in the mean daily weight gain (grams) under semi-intensive (535+9.83) and traditional management systems (TMS) (317+5.46), respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, Saini et al (2014) reported higher DMI (kg/d) in stall fed pre-pubescent camels as compared to grazing group. However, present findings are not in accordance with the findings of Bhakat et al (2009) who determined growth characteristics of Indian camel calves under IMS and SIMS, where they found non-significant intake by using Guar phalgati chara (Cyamopsis tetragonoloba) (6.02 vs. 5.14 kg/calf/d) and significant with moth chara (Phaseolus aconitifolius) (7.91 vs. 6.24 kg/calf/d), respectively. Furthermore, the current study findings are supported by the findings of Tandon et al (1993) who reported that the dry fodder and water intake was positively correlated while the relationship between growth of weaned calves.…”
Section: Discussioncontrasting
confidence: 99%
“…The average growth rate was significantly higher in IMS (611 g/days) than SIMS. Contrary to our observations, Bhakat et al (2009) reported that the ADG (g/day) differed significantly among two systems, with SIMS being higher (325 and 476 g/days) than IMS (278 and 331 g/days) with guar phalgati (Cyamopsis tetragonoloba) and moth chara (Phaseolus aconitifolius) feeding, respectively. In another context, in Sudan, Bakheit et al (2012) studied the effect of management systems on the growth rate of calves and reported that daily growth rate was 534 and 316 g/days in semi-intensive and traditional management systems, respectively.…”
Section: Diet Effect On Growthcontrasting
confidence: 99%
“…Moreover, Saini et al (2014) reported a higher DMI (kg/day) in stall-fed pre-pubescent camels as compared to the grazing group. In the study of Bhakat et al (2009), who determined the growth characteristics of Indian camel calves under IMS and SIMS, a non-significant intake was found by using Guar phalgati chara (C. tetragonoloba) (6.02 vs. 5.14 kg/calf/days), but a significance was found with moth chara (P. aconitifolius) (7.91 vs. 6.24 kg/ calf/days), respectively. Furthermore, in the study of Tandon et al (1993), dry fodder and water intake positively correlated with the growth of weaned calves.…”
Section: Feed Intakementioning
confidence: 99%
See 1 more Smart Citation